2023
DOI: 10.3847/2041-8213/aca769
|View full text |Cite
|
Sign up to set email alerts
|

PHANGS–JWST First Results: The Influence of Stellar Clusters on Polycyclic Aromatic Hydrocarbons in Nearby Galaxies

Abstract: We present a comparison of theoretical predictions of dust continuum and polycyclic aromatic hydrocarbon (PAH) emission with new JWST observations in three nearby galaxies: NGC 628, NGC 1365, and NGC 7496. Our analysis focuses on a total of 1063 compact stellar clusters and 2654 stellar associations previously characterized by the Hubble Space Telescope in the three galaxies. We find that the distributions and trends in the observed PAH-focused infrared colors generally agree with theoretical expectations, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 46 publications
(58 reference statements)
4
21
0
Order By: Relevance
“…Our observed ratios are generally consistent with expectations from the Draine et al (2021) models for PAH size distributions shifted toward larger grains and charge distributions with either "high" or "standard" ionization. This is in agreement with the results from Dale et al (2023) who also find the best alignment with the "large" and "high" ionization results from the Draine et al (2021) model grid, although they use much younger stellar population ages to represent the environments of embedded clusters.…”
Section: Pah-to-continuum Ratiossupporting
confidence: 89%
See 3 more Smart Citations
“…Our observed ratios are generally consistent with expectations from the Draine et al (2021) models for PAH size distributions shifted toward larger grains and charge distributions with either "high" or "standard" ionization. This is in agreement with the results from Dale et al (2023) who also find the best alignment with the "large" and "high" ionization results from the Draine et al (2021) model grid, although they use much younger stellar population ages to represent the environments of embedded clusters.…”
Section: Pah-to-continuum Ratiossupporting
confidence: 89%
“…Our results show variations of the ratio between 0.02 and 0.08, with an average value of ∼0.05 across the three targets. These ratios are investigated in more detail in Chastenet et al (2023) and Dale et al (2023). For comparison, we plot two ratios from the Draine et al (2021) models.…”
Section: Pah-to-continuum Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of PAH abundances have shown that the strength of PAH emission is sensitive to the hardness of the interstellar radiation field, the metal abundance, molecular gas surface density, star-formation activity level (star-formation rate, dust temperature, etc. ), or some combination thereof (e.g., Engelbracht et al 2005;Madden et al 2006;Wu et al 2006;Draine et al 2007;Engelbracht et al 2008;Dale et al 2009;Sandstrom et al 2010;Wu et al 2010;Rémy-Ruyer et al 2015;Chastenet et al 2019;Galliano et al 2021;Dale et al 2023). The LVL sample is a useful testbed for examining how dwarf galaxies and their generally lower metallicities and harder radiation fields affect PAHs.…”
mentioning
confidence: 99%